2005
DOI: 10.1556/avet.53.2005.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of canine platelets on Giemsa- and PAS-stained blood smears

Abstract: The morphology of canine platelets (changes in size, shape, staining characteristics, degree of activation and clump formation, distribution of granules, appearance of vacuoles on Giemsa-stained smears) was investigated in 20 healthy control and 181 diseased dogs. In the group of the sick dogs 84 animals suffered from disorders affecting directly the haematological parameters or the haematopoietic organs such as bleeding, thymic haemorrhage, haemolytic disorders, lymphoma, immune-mediated thrombocytopenia, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Smears are valid to evaluate many parameters that are indicative of platelet function, such as changes in morphology, size, shape, staining characteristics, degree of activation and clump formation, distribution of granules and appearance of vacuoles. 34 In the present study, the PRP smears of Group II showed some deformed, round-shaped platelets which may indicate premature platelet activation. Premature activation would lead to an early release of growth factors, causing them to move to the top of the tube when centrifuged.…”
Section: Resultssupporting
confidence: 45%
“…Smears are valid to evaluate many parameters that are indicative of platelet function, such as changes in morphology, size, shape, staining characteristics, degree of activation and clump formation, distribution of granules and appearance of vacuoles. 34 In the present study, the PRP smears of Group II showed some deformed, round-shaped platelets which may indicate premature platelet activation. Premature activation would lead to an early release of growth factors, causing them to move to the top of the tube when centrifuged.…”
Section: Resultssupporting
confidence: 45%
“…Canine platelet structure and anatomy has been characterized by light and electron microscopy techniques; the latter revealed a more detailed internal structure. For instance, light microscopy showed platelet size and shape and the presence of cytoplasmic processes on the surface of activated platelets [12,13]. Electron microscopy illustrated more specific platelet structures [14] such as alpha, dense, and glycogen granules [15,16] (Figure 1).…”
Section: Structure and Function Of Platelets In Dogsmentioning
confidence: 99%
“…Qualitative analysis of smears is used to evaluate various parameters that are indicative of platelet function, such as changes in morphology, size, shape, staining characteristics, degree of activation and clump formation, distribution of granules, and appearance of vacuoles. [ 19 ] In this study, the morphology of platelets was worst in the samples from vials containing EDTA. This may be attributed to the destructive effect of EDTA on platelets.…”
Section: Discussionmentioning
confidence: 79%